Importance of ICT: Teaching and Learning Enrichment: Exploring the Impact of ICT in the Teaching-Learning Process (Journal of Advances and Scholarly Researches in Allied Education, 2021)
There are certain unavoidable facts that need to be taken care of when we talk about the current trends and innovations in our system of education. Many educational reformations are also taking place. One amid is Information and Communication Technology (ICT). ICT stands for information and communication technology. ICT include the use of hardware and software for efficient management of information and it also includes communication devices like radio, television, cell phones, computer, satellite systems and many more. It refers to that technology which is used to transmit, store, share, create or exchange information. Innovations in technology and globalization have leaded to an enlarged the use of ICTs in all sectors. In modern era, the world is moving rapidly towards digitalisation such as e-governance, e- health, e- education etc. The function of ICT in education has developed into more important and this importance will continue to raise and expand in 21st century. It has added a facet to learning that was not available beforehand. With the incorporation of ICT in educational sector, the customary forms of teaching and learning are changed into online and virtual environment. ICT can endow with universal access to education, helps in professional development of the teacher, the delivery of quality teaching-learning, equity in education, more efficient educational management, governance and administration. The increasing use of information and communication technologies (ICTs) has revolutionized the teaching-learning process in the 21st century. The use of ICT in education not only improves classroom teaching learning process, but also provides the facility of e-learning and distance learning to the learners. It is commonly believed that ICTs can be proved supportive in empowering teachers and learners, making important contributions in educational field. In the present era, everyone can have access to teaching material at own level and consult many experts by video conferencing from all over the world. Currently, a teacher is been teaching his students through the use of ICT even though they are geographically scattered. People are using ICT in every walk of life for their various purposes and also from higher educational books to online courses that all are beneficial for the learners in 21st century. We can’t imagine a day without ICT. Today, world without ICT means we do not have any information about the events that are occurring around. It has become a part and parcel of life. Thus, present paper will highlight the urgency and needs of ICT in teaching learning process. The researcher will also highlight the key challenges of educational sector at present time.